Low-level laser therapy applied by nurses: What is their scenario of action and uniformity of therapeutic parameters? (Research, Society and Development, 2023)
Objective: To identify and analyze the scientific productions available in the literature in which the nurse has been working within laser therapy, and the challenges encountered in obtaining therapeutic parameters used in LLLT for safe clinical practice. Method: This is an Integrative Review, carried out through an online search carried out between the months of July and August 2023, including scientific articles, selected, and published from 2018 to 2023, in Portuguese, English and Spanish in the databases of Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library (SciELO), and in the Nursing Database (BDENF). Results: 9 articles were included between 2018 and 2022, all of which were published and carried out in Brazil. Regarding the types of studies, each author used a methodology, which were randomized clinical trials, integrative review, review of reported cases, experience report, and systematic review. With emphasis on the use of laser by nurses, the setting of action and which dosimetry protocol they are using in the consultations. Conclusion: Through this review, the study made it possible for nurses to remain focused on the use of this therapeutic proposal for treatments aimed at skin lesions, such as pressure ulcers, venous ulcers, and diabetic foot. It demonstrated the need for more prospective studies on laser dosimetry in the context of nurses' work in therapy for skin lesions.